Proceso de atención de enfermería en paciente femenina de 64 años de edad con diagnóstico de hiperplasia adenomatosa del endometrio. - Villacrés Sandoya, Nohelia Alejandra (2023)
Endometrial adenomatous hyperplasia is a pathology that affects the endometrium, and is nothing more than the increase in size of this organ, it is considered a public health problem since it is one of the most common causes of endometrial or endometrial cancer. The present clinical case describes a 64-year-old female patient, diagnosed with endometrial adenomatous hyperplasia, who went to the emergency room, the symptoms presented by the patient were abdominal pain and excessive bleeding, The patient was seen in an outpatient clinic, which with the complementary examinations and pathological history led us to this diagnosis and in turn to be able to make our evidence-based nursing diagnosis, and finally hospitalized for a surgical procedure, which with the complementary examinations and pathological history led us to this diagnosis and in turn to be able to make our evidence-based nursing diagnosis.